Information Technology Capital Expenditure Analysis Using Cobb Douglas Production Function at PT. XL Axiata Tbk - Yudistira, Muhammad Kevin; Abdurrahman, Lukman; Santoso, Ari Fajar (eProceedings of Engineering, 2023)
Abstract-Information technology investment refers to the complete life cycle costs of all or a portion of an IT project, including ongoing expenses incurred after the project or system has been put into place. An IT-based corporation, PT XL Axiata, served as the case study in this study and the research topic. The goal is to determine how IT investment value affects the success of PT and other information technology-based businesses. OneXL Axiata. means that the organization has increased the amount of IT investments that it has made. From XL Axiata's annual report for the period of 15 years from 2006 to 2020, the data used for this study was derived. The Equity variable (K), the Manpower variable (L), and the TI capex variable (I) are the variables used in this study. With the help of multiple linear regression and nonlinear regression techniques, this study's Cobb Douglas production function was examined. After doing the research, findings were acquired utilizing the multiple linear regression method since the difference was found to be 0.05% close to the actual value of income. Additionally, the research utilizing the Cobb doubleglass production function yielded a value of 0.378 for the IT investment made by Bank Mandiri over the course of the last 15 years. With a TFP value of 2433,328 > 1, the investment value has a high productivity.Keywords- cobb douglas, IT Investment Value, XL Axiata, SPSS, Regression.